3D Evaluation of the Relationship between Different Vertical Growth Patterns and Cranial Base Angulations - Ugurlu, Mehmet; Oksayan, Rıdvan; Bayrakdar, Ibrahim Sevki; Kahraman, Fatih; Dagsuyu, Ilhan Metin; Aydın, Mehmet; Orhan, Kaan (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective This study aimed to compare cranial base angulations in subjects with high-angle, low-angle, and normal-angle vertical growth patterns using cone beam computed tomography (CBCT).Design This study is a retrospective clinical research.Settings This study was carried out at the Dentistry Faculty of Eskisehir Osmangazi University.Participants According to skeletal vertical face growth patterns, 78 subjects (48 females and 30 males, average age: 13.19 ± 1.73 years) were divided equally into three groups: high angle, low angle, and normal angle groups.Main Outcome Measures Cephalometric images were derived from CBCT, and patients were classified according to the SN-GoGn angle (sella-nasion, gonion gnathion angle). Sagittal, axial, and coronal cranial base angulations were measured in three-dimensional (3D) CBCT images. Data were analyzed using the Kolmogorov–Smirnov normality, Kruskal–Wallis, and Mann-Whitney U statistical tests.Results There were statistically significant differences between the low-angle and high-angle groups according to sagittal cranial base angulation parameters (p = 0.01). Conversely, there were no statistically significant differences between vertical facial growth patterns according to coronal and axial cranial angle variables (p > 0.05).Conclusion According to the study results, there were no effects of cranial base angulations in two planes (coronal and axial) on different vertical skeletal growth patterns. In the sagittal cranial base angulation parameter, the high-angle group showed greater angulation values than the low-angle group. CBCT may be helpful for evaluating, diagnosing, and predicting 3D cranial base differences.
Keywords: Cranial Base; three-dimensional; cone beam computed tomography; vertical face growth